Can pathological reports of rectal cancer provide national quality indicators?. Issue 9 (23rd March 2018) - Keane, Celia; Lin, Anthony Y.; Kramer, Nicole; Bissett, Ian
Abstract : Background: Rectal cancer care has become increasingly complex and requires accurate information. The pathology report is a vital tool for accessing information to gauge a patient's prognosis and to guide treatment decisions. The aim of this study was to assess the quality of histopathological reporting and surgery for rectal cancer in New Zealand using defined quality indicators. Methods: This is a retrospective audit of pathological reports of all resected rectal cancer pathology reports submitted to the New Zealand Cancer Registry (NZCR) in 2015. The quality of reporting was assessed using specified criteria: synoptic report, adequate lymph node retrieval, reporting of circumferential resection margin (CRM) and mesorectal excision quality. Surgical outcomes were sphincter preservation rate, CRM clearance and complete mesorectal excision. Results: A total of 803 patients with rectal cancer were reported to the NZCR in 2015, 505 underwent proctectomy. A total of 89.5% of reports were structured, 81.8% reported mesorectal excision quality and 86.7% reported CRM status. Adequate lymph node retrieval was obtained in 65.1%, complete mesorectal excision in 84.6% and positive CRM in 6.2% of cases. Quality varied between laboratories and district health boards. High‐volume laboratories had higher quality reporting. Surgeon volume and training was related to adequate lymph node retrieval but not CRM clearance nor mesorectal excision quality. Conclusion: High‐quality pathological reporting is associated with the use of synoptic reporting templates. Surgical outcomes for rectal cancer in New Zealand, especially the low rate of CRM involvement, compare favourably with international audits.